PPP Paradox: Promise and Perils of Public-Private Partnership in Education - Agrawal, Poonam; Singh, Abhishek (INDIAN EDUCATIONAL REVIEW, 2013)
Reform in education is a constant endeavour. Introduction of PPP in education is being seen as one of the most desirable reforms when there are issues related with widening the reach and addressing the quality. The XI Five Year Plan of the Government of India records the benefits of PPP in education at many places in its document, thus encouraging the relevant initiatives. However, there is also certain skepticism at various quarters attached with it as far as education, at least the school education, is primarily considered a Government’s responsibility and the private sector is known for its leanings towards profits. In this context the book has come up very timely on this subject, very aptly dealing with the difference between privatisation and partnership, as mixing the two together may lead to misconceptions. Further, while advocating in favour of PPP, the author is cautious that ‘social/public’ nature of educating people is not threatened. In her own words “While I argue for the PPP, I maintain a critical stance throughout the book and am careful to enumerate the pitfalls and challenges that line the path of partnerships in education…. I argue that promise outweighs theperils.”